Pengaruh Profesionalitas Kerja Pegawai Terhadap KualitasPelayanan Masyarakat di Kantor Camat Kampar Kiri Tengah - Septrian Nurhalizah; Ikhwani Ratna (Yayasan Almanar Pujud, 2024)
This study aims to determine the effect of employee work professionalism on the quality of public service at the Kampar Kiri Tengah District Office. The research method used in this study is quantitative. The population in this study were all people who had provided services in the last 2 months of 2023 at the Kampar Kiri Tengah District Office totaling 350 people. The sampling method used in this study was saturated sampling. The data source used in this study was primary data obtained directly from the answers to questions in the questionnaire distributed to respondents. The data was analyzed using the simple linear regression method and processed using the SPSS version 29 program. The results of this study indicate that based on the t-test (partial) the calculated t value obtained for the Professionalism variable was 4.595 <t-table value of 1.991, the results of the hypothesis test showed that the calculated F value was 21.118> F table 3.97 and the sig value was 0.001, which is lower than <0.05. The correlation coefficient value of Professionalism is 0.466 so it can be categorized as having a fairly strong correlation level. So it can be concluded that there is a positive relationship between the Professionalism variable (X) and the Public Service Quality variable (Y).